Demystifying the Mystery of Vitamin B12 Deficiency in an Infant with Developmental Delay - Heba Ali Aldarawsha; Sura Ahmed AlDoory; Shafiqa Mohamed Saleh; Nidheesh Cheeyancheri Chencheri (Dubai Medical Journal, 2022)
A 7-month-old boy presented to our hospital with complaints of epistaxis. Pancytopenia was found on a blood test, and physical examination was significant for hepatosplenomegaly, acral hyperpigmentation of hands and feet, and hypotonia, along with mild delayed milestones. The infant underwent extensive investigations including metabolic workup and bone marrow aspiration, which revealed abundant megalocytes. Vitamin B12 was deficient (result 82 pg/mL, reference range 187–883 pg/mL); therefore, vitamin B12 therapy was commenced. Following the initiation of vitamin B12 therapy, blood cell lines normalized, neurological symptoms improved, hepatosplenomegaly regressed, and milestones were achieved.